A method to standardize the blood flow restriction pressure by an elastic cuff. (9th December 2018) - Abe, Takashi; Mouser, J. Grant; Dankel, Scott J.; Bell, Zachary W.; Buckner, Samuel L.; Mattocks, Kevin T.; Jessee, Matthew B.; Loenneke, Jeremy P.
Abstract : Blood flow restriction training using a practical (non‐pneumatic) elastic cuff has recently increased in popularity. However, a criticism of this method is that the pressure applied and the amount of blood flow restriction induced is unknown. The aim was to quantify blood flow following the application of an elastic cuff and compare that to what is observed using a more traditional pressurized nylon cuff. Thirty‐five young participants (16 men and 19 women) visited the laboratory once for testing. In a randomized order (one condition per arm), an elastic cuff (5 cm wide) was applied to one arm and blood flow was measured following the cuff being pulled to two distinct lengths; 10% and 20% of the resting length based on arm circumference. The other arm would follow a similar protocol but use a pressurized nylon cuff (5 cm wide) and be inflated to 40% and 80% of the individuals resting arterial occlusion pressure. There was a main effect of pressure for blood flow with it decreasing in a pressure‐dependent manner (High < Low, P < 0.001). The mean difference (95% CI) in blood flow between cuffs was −5.9 (−18.9, 7.0) % for the lower pressure and −4.0 (−13.2, 5.1) % for the higher pressure. When the relative changes for each cuff were separated by sex, there were no differences in the changes from Pre ( P ≥ 0.509). The application of a pressure relative to the initial belt length, which is largely dependent upon arm circumference, appears to provide one method to standardize the practical blood flow restriction pressure for future research.